2006
DOI: 10.1523/jneurosci.2102-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

M1Muscarinic Receptors Inhibit L-type Ca2+Current and M-Current by Divergent Signal Transduction Cascades

Abstract: 2 )], whereas M-current did not. Western blot and imaging studies confirmed acute activation of cPLA 2 by muscarinic stimulation. Third, in type IIa PLA 2 [secreted (sPLA 2 )] ؊/؊ / cPLA 2 ؊/؊ double-knock-out SCG neurons, muscarinic inhibition of L-current decreased. In contrast, M-current inhibition remained unaffected but recovery was impaired. Our results indicate that L-current is inhibited by a pathway previously shown to control M-current over-recovery after washout of muscarinic agonist. Our findings s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
89
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(99 citation statements)
references
References 54 publications
10
89
0
Order By: Relevance
“…Among the mAChRs, M 1 is most abundantly expressed in the hippocampus, cortex, and striatum, and localizes to postsynaptic membranes (3), where it signals via G q /G 11 G-proteins to phospholipase C and through other G-proteins to additional signaling systems (4,5). M 1 regulates several ion channels including KCNQ inwardly rectifying K ϩ currents, voltage-gated calcium channels, and NMDA receptors (4)(5)(6)(7)(8)(9). Thus M 1 could mediate much of the cognitive effects of ACh.…”
mentioning
confidence: 99%
“…Among the mAChRs, M 1 is most abundantly expressed in the hippocampus, cortex, and striatum, and localizes to postsynaptic membranes (3), where it signals via G q /G 11 G-proteins to phospholipase C and through other G-proteins to additional signaling systems (4,5). M 1 regulates several ion channels including KCNQ inwardly rectifying K ϩ currents, voltage-gated calcium channels, and NMDA receptors (4)(5)(6)(7)(8)(9). Thus M 1 could mediate much of the cognitive effects of ACh.…”
mentioning
confidence: 99%
“…The depression causes 20-60% inhibition of the current and there is no delay of L-type channel activation [15,18,39,40]. In Table 1 of ref [23] are listed a number of papers showing evidence for a V-independent GPCR-mediated inhibition of L-type Ca 2+ currents in neurons and neuroendocrine cells to which should be added the recently reported effect of muscarinic agonists on sympathetic neurons [41]. This latter further broaden the number of cell preparations in which the inhibition of L-type channels occurs: sensory, peripheral and central neurons, as well as ␤-pancreatic, chromaffin, adrenal glomerulosa and pituitary cells.…”
Section: Direct Inhibition Of L-type Channels By G Proteinsmentioning
confidence: 99%
“…The authors proposed that depletion of PIP 2 on the plasma membrane is the cause of the G q receptormediated slow inhibition of Ca V currents in neurons. In contrast, Rittenhouse and colleagues (13,14) reported that arachidonic acid mediates the muscarinic inhibition and an associated enhancement of N-type Ca 2+ current in rat sympathetic neurons. The muscarinic modulation was attenuated when arachidonic acid production by PLA 2 was blocked.…”
mentioning
confidence: 90%
“…An intriguing aspect of Ca V channels is their slow, voltage-independent modulation by G q protein-coupled receptors (G q PCRs) (2)(3)(4)(5). The several proposed mechanisms for this slow modulation of Ca V channels include depletion of phosphatidylinositol 4,5-bisphosphate (PIP 2 ) via activation of phospholipase C (3-10), phosphorylation by protein kinases (11,12), generation of arachidonic acid by phospholipase A 2 (13,14), and other unspecified pathways involving Gα q or Gβγ-subunits (15,16). In the nervous system, the dissection of G q PCR modulation of Ca 2+ channels is made difficult by the generation of several second messengers and by the existence of multiple subtypes of Ca V channels.…”
mentioning
confidence: 99%